Practical report: Ministry of Domestic Trade, Co-Operative & Consumerism (MDTCC) in Kudat, Sabah / Rellyn Neena Allen James - Allen James, Rellyn Neena (Universiti Teknologi MARA, Sarawak, 2014)
The Ministry of Domestic Trade, Co-Operative & Consumerism (MDTCC) was formerly known as the Ministry of Domestic Trade and Consumerism Right. It was a Ministry of Malaysia which was established on 27 October in 1990 to encourage the development of domestic trade as well as to increase the effective protection to consumer right. The latest minister of the Ministry of Domestic Trade, Co-Operative & Consumerism is Dato’ Haji Hassan Malek. These were followed by the changing in the government fundamental leader of Dato’ Sri Najib Tun Razak on Mac 2009 and since 11 Jun 2009, KPDNHEP now known as The Ministry of Domestic Trade, Co-Operative & Consumerism. This is regarding the elimination ofthe Ministry of Business Development and Co-Operative. The Ministry of Domestic Trade, Co-Operatives & Consumerism (MDTCC) (Malay: Kementerian Perdagangan Dalam Negeri, Koperasi Dan Kepenggunaan) is a ministry which established under the Malaysian government, and led by the incumbent Minister of Domestic Trade, Co-Operatives & Consumerism. MDTCC formulates policies, strategies and reviews matters related to the development of domestic trade and consumerism.